The Role of Technostress on the Relationship between Information Technology Mindfulness and Employee Well-Being - Intapunya, Dew; Kanu Priya Mohan (Thailand and The World Economy, 2025)
The COVID-19 pandemic affected Thailand’s economy at a macro level and impacted work lives of individuals at a micro level. Since many organizations changed the work policy to remote working and work from home, it resulted in deteriorating work well-being. Research showed that employees were forced to spend extended hours in front of computers, triggering stress due to excessive technological use, or ‘technostress.’ This study explored technostress and its role in the relationship between information technology mindfulness (IT mindfulness) and employee well-being, measured in two dimensions: affect and job satisfaction. The current study is the SEM analysis using data from 220 IT users at work to study the interrelationship among technostress, IT mindfulness, affect, and job satisfaction. The results showed that technostress has a negative effect on affect (β = -.59, p < .01) and on job satisfaction (β = -.39, p < .01). Additionally, technostress has a mediating role in the relationship between IT mindfulness and affect (β= .22, p < .05). The findings can be applied to generate awareness in organizations and help in developing effective strategies to alleviate work stress due to the extreme use of technology.